Metal-Free tert-Butyl Hydrogenperoxide (TBHP) Mediated Radical Alkylation of Enol Acetates with Alcohols: A New Route to β-Hydroxy Ketones - Tang, Yucai; Fan, Yuanyuan; Zhang, Ye; Li, Xiaoqing; Xu, Xiangsheng (Synlett, 2016)
A metal-free TBHP-mediated radical alkylation of enol acetates with alcohols is described. This method provides a new route to a variety of β-hydroxy-ketones in moderate to good yields.
Keywords: metal-free; radical alkylation; enol acetates; alcohols; β-hydroxyketones